Modelling Game as Socio-Psychological Paradigm for Resolving Ethno-National Conflicts - Bocheliuk, Vitalii I.; Zaytseva, Valentyna M.; Gugnin, Eduard A.; Arabadzhyiev, Dmytro Yu.; Popovych, Vasyl M. (International Journal of Criminology and Sociology, 2021)
The aim of this study was: (a) to evaluate the effectiveness of training to improve the intercultural behaviour of students; (b) to study and enrich their personal experience of resolving interethnic and international conflicts; and (c) to identify factors that contribute to the effective development of relevant skills that ensure social self-efficacy, reduce social avoidance, increase empathy and intercultural tolerance. The study used general scientific theoretical, empirical, experimental and statistical methods. To diagnose the dynamics of the studied variables – social self-efficacy, social avoidance, empathy, intercultural tolerance – “Scale of social self-efficacy of Fan and Mak”, “Situational scale of social avoidance”; checklists “Interpersonal skills”; “Basic scale for the diagnosis of empathy in adults”; diagnosis of the level of formation of intercultural tolerance were used. At the experimental stage of the study, a series of training based on modelling games (simulations) to resolve ethno-national conflicts was conducted. At the end of the training, a repeated diagnostic section of the dynamics of the above-mentioned variables and a semi-structured interview was conducted, which included 5 open-ended questions. The multivariate analysis of variance (MANOVA) of these variables in comparison with EG and CG groups revealed significant dynamics in the variables “social self-efficacy”, “empathy”, “intercultural tolerance” and minor changes in the variable “social avoidance”. The dynamics of the EG index was more significant. Respondents also praised the types of work such as working in groups, the model of providing feedback during game situations and presentations of student projects. The results of this study confirmed that the model based on simulation games (simulations) for resolving ethno-national conflicts was effective in improving social self-efficacy, empathy and intercultural tolerance and in lowering psychological barriers (social avoidance) of EG participants compared to CG individuals. Participants reported that this type of training allowed them to develop skills for future professional activities in a multicultural (poly-ethnic or poly-national) community.